Aprendizagem e pandemia: análise das políticas de avaliação implementadas no estado do Rio Grande do Sul - Guimarães, Carine Pistoia (2023)
This study is linked to the Professional Master's Degree in Public Policies and Educational Management from the Federal University of Santa Maria, in the line of research on Basic and Higher Education Policies and Management, and to the Study Group on Education, Technologies and Society (INTERFACES/ CNPq). It seeks to understand the constitutive movement of the implemented policies by the government of the State of Rio Grande do Sul to evaluate the performance of students in the first cycle of Elementary School upon returning to post-pandemic classes. As a reference, it presents the theoretical and legal frameworks of the promoted assessment policies in the state and brings important elements to the debate about post-pandemic student learning. It was chosen a case study in a qualitative perspective. To analyze the evaluation policies implemented at federal and state level, documentary research was essential. For the research instruments, the following were chosen: semi-structured interviews; observation and logbook. The data was analyzed through Discursive Textual Analysis, from which the following categories emerged: The actions of the government of Rio Grande do Sul to evaluate post-pandemic students from the perspective of educators, where the importance of knowing the public policies that guide the evaluations promoted by the state government in the return to face-to-face education is highlighted, as well as presenting the knowledge and educators’ perceptions regarding the promoted policies there; Post-pandemic school context and strategies for teaching and learning aligned with the BNCC, which presents the post-pandemic school scenario, the difficulties faced and seeks to identify strategies to develop a learning process for children in the first year of Elementary School aligned with the skills and competencies provided for the BNCC; and Perspectives of the 2030 Agenda and SDG 4: educators challenges, which seeks to elucidate how the public policies proposed by the government align with SDG 4, of the 2030 Agenda, regarding to ensure equitable and quality learning for all. The product of the research was a Learning Workshop in a state school to provide to the students a space to reframe knowledge that was no longer developed during the pandemic. It is concluded that there is a distance between teachers and the state government in relation to the difficulties presented by post-pandemic students, therefore, there is a lack of continuing education processes to strengthen these ties and together build a more inclusive, efficient, and quality education. This dialogue would make it possible to develop actions in favor of the student, towards achieving the goals of SDG 4, referring to the goals for Education.